2022
DOI: 10.1088/1755-1315/949/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

State regulation of investment in agriculture

Abstract: An important task of state regulation of investment in the agricultural sector of the economy is to attract investors who are able to increase the efficiency of the functioning of agricultural enterprises. The success of the functioning of this enterprise depends on how quickly an agricultural enterprise is able to adapt to changes in the external environment. This is achievable under the condition of the most optimal use of the enterprise’s resource potential. Small agricultural enterprises are usually depriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…With the same utility function for a more conservative investor , the value of the return and risk R will be less than the value of the risk propensity of a more risk -prone investor . Therefore, according to (5), for a conservative investor, 𝑒 − 𝑅 * 𝑥 𝛼 2 will be more than for an investor more prone to risk. Thus, a more conservative investor perceives an investment in this enterprise as more profitable than a riskier investor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the same utility function for a more conservative investor , the value of the return and risk R will be less than the value of the risk propensity of a more risk -prone investor . Therefore, according to (5), for a conservative investor, 𝑒 − 𝑅 * 𝑥 𝛼 2 will be more than for an investor more prone to risk. Thus, a more conservative investor perceives an investment in this enterprise as more profitable than a riskier investor.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a more conservative investor perceives an investment in this enterprise as more profitable than a riskier investor. In addition, taking into account (5), it can be concluded that if the utility functions coincide, then the competitiveness of the enterprise seems to be higher to a conservative investor than it would seem to a riskier investor.…”
Section: Discussionmentioning
confidence: 99%